15 questions and answers about pediculosis capitis. Pediculosis pubis. - Scanni, G.; Porcelli, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
Is it true that pediculosis capitis affects poor and dirty people? No, it is not true. Mummified head lice have been found on the hair of Pharaoh mummies (8) and pediculosis capitis is widespread in all developed countries. This prejudice is responsible for severe psychological trouble in the affected families, thus discouraging the reporting of new cases and eradicating of epidemics. What about the morphological characteristics of head lice? [...]